Stages and Characteristics of Development in Chinese International Student Education Over a 70-Year Period, 70年来来华留学生教育的发展历程与基本特征 - Li, Lijie (Journal of International Students, 2020)
This study discussed international education in China from the perspectives of social background, policies and regulations, guiding principles, enrolment scales and admission levels. Based on the discussion, the study proposed seven development stages of China’s international student education, i.e. start-up, stagnation, recovery, exploration and development, expansion of development, regulation of the development, and improvement of quality and efficiency. The study also revealed the characteristics of international education development in China, i.e. the increasingly diverse factors driving the changes of international education policy, and the increasing number of international students, particularly those from “Belt and Road” countries and those pursuing degree education. Recommendations are given for the further development of international education in China. 从来华留学生教育发展的时代背景、政策法规、指导思想、招生规模、招生层次等出发，系统梳理来华留学生教育的发展脉络，将中华人民共和国成立70年来的来华留学生教育发展过程分为启动、停滞、恢复、探索发展、扩大发展、规范管理、提质增效7个阶段。70年来，来华留学生教育表现出了如下一些特征：政策制定动因由单一转向多元；来华留学生规模不断扩大，“一带一路”沿线国家的留学生仍是主力；生源结构持续调整与优化，学历层次不断提高。在此基础上，为加快推动来华留学生教育改革发展，提出了构建符合中国发展阶段、文化特征和时代特点的来华留学生教育政策建议。